Price Dynamics of Swedish Pharmaceuticals - Aljoscha Janssen (Research Institute of Industrial Economics (IFN), 2020)
This paper investigates price patterns of off-patent pharmaceuticals in Sweden. I show that price dynamics are dependent on the number of competitors in the market. The price patterns follow predictions from a model of dynamic price competition in which the demand for pharmaceuticals incorporates the known biases of consumers: habit persistence and brand preferences. Using the regulated market of Swedish pharmaceuticals, I show that price may help in identifying possible tacit collusion by manufacturers in markets where consumers experience behavioral frictions.
Keywords: D43; I11; L13; L40; 330; Pharmaceutical pricing; Dynamic oligopoly; State dependence; Price cycles